2007
DOI: 10.1614/wt-06-185.1
|View full text |Cite
|
Sign up to set email alerts
|

Sulfentrazone Adsorption and Mobility in Surface Soil of The Southern United States

Abstract: Sulfentrazone adsorption and mobility in six soils with varying soil properties were evaluated under laboratory conditions. Adsorption was evaluated using a modified slurry technique. Mobility was evaluated using packed-soil columns under saturated flow conditions. The order of adsorption to soil was Sequatchie loam > Dothan loamy sand = Bosket fine sandy loam > Malden loamy sand > Commerce silty clay loam > Harkey clay loam. Greater sulfentrazone adsorption occurred in soils with lower pH. Sulfentrazone movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 22 publications
1
27
0
1
Order By: Relevance
“…Estes resultados podem ser justificados devido ao fato de o flumioxazin (Kow 2,55), metolachlor (Kow 3,05) e sulfentrazone (Kow 1,48) apresentarem va- (Oliveira et al 1998, Liu et al 2001, Ohmes & Mueller 2007, Szmigielski et al 2009). Biffe et al (2010) verificaram que o S-metolachlor (1.920 g ha -1 ) foi seletivo para as cultivares 'Fécula Branca' e 'Fibra', quando aplicado em pré--emergência, em condições de solo arenoso.…”
Section: Methodsunclassified
“…Estes resultados podem ser justificados devido ao fato de o flumioxazin (Kow 2,55), metolachlor (Kow 3,05) e sulfentrazone (Kow 1,48) apresentarem va- (Oliveira et al 1998, Liu et al 2001, Ohmes & Mueller 2007, Szmigielski et al 2009). Biffe et al (2010) verificaram que o S-metolachlor (1.920 g ha -1 ) foi seletivo para as cultivares 'Fécula Branca' e 'Fibra', quando aplicado em pré--emergência, em condições de solo arenoso.…”
Section: Methodsunclassified
“…Lower control of Palmer amaranth with F7583 applied preplant at Manhattan compared to Hays could be due to higher weed density (data not shown) and lower soil pH (6.8) than at Hays (7.8). Greater sulfentrazone adsorption occurs in soils with lower pH [10]. Sulfentrazone is a weak acid and its concentration in soil solution increases as soil pH increases and is available for root uptake by plants [11].…”
Section: Palmer Amaranth Controlmentioning
confidence: 99%
“…Evaluating the sulfentrazone herbicide behavior in soil, Szmigielski et al (2009) observed that this herbicide presents a high bioactivity in soils with low tenor of organic matter and clay, where its residual activity could overcome 302 days, fact also observed by Blanco & Velini (2005). To Ohmes & Mueller (2007), the sulfentrazone sorption is more intense in clayvey soils.…”
Section: Greenhouse Experimentsmentioning
confidence: 80%